2017
DOI: 10.1051/matecconf/201712502002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sustainable Practices within Project Management Methods

Abstract: Abstract. The purpose of this research study is to investigate some of the sustainable practices within projects with a focus on social projects. The different research methodologies applied through this research consisted both primary and secondary research, including literature review and through case study. The stakeholder's behavioural needs towards acting and implementing sustainable practices led to the adoption of sustainable practices within projects which are managed across profit and non-profit organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Farmers should be taught using practical demonstration rather than theory. The respondents indicated that farmers should be encouraged to use environmentally friendly inputs such as organic fertilizers and other safe production inputs; this assertion is confirmed by Shah, Ganji and Coutroubis (2017). The innovation should first be tested or researched and thereafter be shared with farmers.…”
Section: Promoting Sustainable Agriculturementioning
confidence: 83%
“…Farmers should be taught using practical demonstration rather than theory. The respondents indicated that farmers should be encouraged to use environmentally friendly inputs such as organic fertilizers and other safe production inputs; this assertion is confirmed by Shah, Ganji and Coutroubis (2017). The innovation should first be tested or researched and thereafter be shared with farmers.…”
Section: Promoting Sustainable Agriculturementioning
confidence: 83%
“…In recent years, businesses around the world, especially SMEs have started giving credit to sustainable pillars in order to move towards continuous improvement and innovation. Enabling the adoption and improvement of the major organisational aspects such as economic, social and environmental performance is a major challenge for many companies, and hence, sustainability strategy is hugely important towards the transformation of the business and future prosperity (Shah et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many countries are seeking to enhance their business infrastructure in order to benefit their economy towards adoption of sustainable practices. However, even though the environmental sector is growing rapidly, this is a long and costly process which requires fundamental transformational changes at different levels of the organisation (Shah et al , 2017). Hence, many gaps have not been explored towards the implications of the change and that of the effects of adopting better greener and environmental changes within the organisations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations